Somatic Expression of PyMT or Activated ErbB2 Induces Estrogen-Independent Mammary Tumorigenesis - Toneff, Michael J (Neoplasia Press Inc., 2010)
Estrogen signaling is required for the proliferation of normal breast epithelial cells. However, prophylactic inhibition of estrogen signaling fails to prevent 56% of human breast cancer cases. The underlying mechanism is not well understood. Aberrant activation of growth factor signaling is known to provide alternative proliferation pathways in breast cells that are fully transformed, but it is not known whether activation of growth factor signaling can substitute for estrogen signaling in causing aberrant proliferation in the normal breast epithelium. Here, we report that in a retrovirus-based somatic mouse model (replication-competent ALV-LTR splice acceptor/tumor virus A) that closely mimics the evolution of sporadic human breast cancers, mammary epithelial cells harboring PyMT or activated ErbB2 evolve into tumors independent of estrogen or other ovarian functions in contrast to previous observations of estrogen-dependent cancer formation in germ line mouse models of ErbB2 activation. Importantly, ErbB2 activation in normal mammary cells causes estrogen-independent proliferation in both estrogen receptor (ER)-negative cells as well as in normally quiescent ER-positive cells. Therefore, aberrant activation of growth factor signaling contributes to estrogen-independent proliferation of both preneoplastic and cancerous mammary cells, and prophylactic therapy against both growth factor signaling and estrogen signaling may need to be considered in women with increased risk of breast cancer.